Biofilm Formation and Detection of the icaA Gene in Staphylococcus Aureus Isolates from Ocular Infections - Karar Abdulkhuder; Mahmood Awad (International Journal of Clinical and Experimental Medical Sciences, 2026)
Background: Staphylococcus aureus is a major opportunistic pathogen implicated in various infections, including ocular infections. One of its key virulence factors is the ability to form biofilms, which are structured bacterial communities embedded in a self-produced extracellular matrix. Biofilm formation enhances bacterial survival under adverse conditions, including antibiotic exposure and host immune defenses, thereby contributing to chronic and recurrent infections. Aim: This study aimed to evaluate the biofilm-forming ability of S. aureus isolates obtained from ocular infections using the Congo Red Agar (CRA) method and to detect the presence of the biofilm-associated icaA gene using polymerase chain reaction (PCR). Methods: A total of 35 clinical isolates of S. aureus were included in this study. Biofilm formation was assessed phenotypically using the Congo Red Agar (CRA) method. Based on the results, isolates were categorized into strong, moderate, weak, and non-biofilm producers. Additionally, PCR was performed on 10 selected isolates to detect the presence of the icaA gene, a key determinant involved in biofilm formation. Results: Out of the 35 isolates, 10 (28.6%) exhibited strong biofilm formation, 15 (42.8%) showed moderate formation, 5 (14.3%) demonstrated weak formation, and 5 (14.3%) were non-biofilm producers. Overall, 71.4% of the isolates displayed varying degrees of biofilm production, indicating a high prevalence of this virulence trait. PCR analysis revealed that 7 out of 10 tested isolates (70%) were positive for the icaA gene. A correlation was observed between phenotypic biofilm formation and the presence of the icaA gene. Conclusion: The findings demonstrate a high prevalence of biofilm-forming S. aureus isolates in ocular infections and highlight the role of the icaA gene in biofilm production. The observed correlation between phenotypic and genotypic methods suggests that molecular detection can serve as a reliable complementary tool. Identification of biofilm-producing strains is essential for improving treatment strategies and reducing the risk of persistent and recurrent infections associated with biofilm-mediated antibiotic resistance.